2015
DOI: 10.1007/s00284-015-0813-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-spinning of Silver Nanoparticles with Nisin Increases the Antimicrobial Spectrum of PDLLA: PEO Nanofibers

Abstract: Silver nanoparticles (AgNPs), synthesized using N,N-dimethylformamide (DMF), were electrospun with nisin in a 50:50 blend of 24 % (w/v) poly(D,L-lactide) (PDLLA) and poly(ethylene oxide) (PEO). Addition of AgNPs decreased the average diameter of the nanofibers [silver nanofibers (SF)] from 588 ± 191 to 281 ± 64 nm, or to 288 ± 63 nm when nisin was co-spun with AgNPs. Nanofibers containing AgNO3 (SF) had a beads-on-string structure, whereas nanofibers with AgNPs and nisin [silver plus nisin nanofibers (SNF)], n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…In comparison with pure PVP, the conductivity of PVP/AgNO 3 -0.34% increased by 32%, while the AFD decreased by 37% (Table 1). The increased electrical conductivity led to increased surface charge of the polymer jet, and thus, stronger elongation forces were imposed to the jet, resulting in defect-free, more uniform fibers with a thinner diameter distribution [29,37]. Based on the conductivity and viscosity of solution above, it was concluded that PVP/CNC-4%/AgNO 3 -0.34% had the smaller diameter owing to the higher conductivity and controllable rheological properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with pure PVP, the conductivity of PVP/AgNO 3 -0.34% increased by 32%, while the AFD decreased by 37% (Table 1). The increased electrical conductivity led to increased surface charge of the polymer jet, and thus, stronger elongation forces were imposed to the jet, resulting in defect-free, more uniform fibers with a thinner diameter distribution [29,37]. Based on the conductivity and viscosity of solution above, it was concluded that PVP/CNC-4%/AgNO 3 -0.34% had the smaller diameter owing to the higher conductivity and controllable rheological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles could be more efficiently formed to deliver themselves to target organisms [33]. Studiess on the electrospun Ag nanoparticle-embedded polymer nanofibers using the mixture of AgNO 3 precursor and polymer solutions, i.e., PVA [34], PVP [3,33], poly (lactide- co -glycolide) (PLGA) [35], PEO [36,37], and PAN [38,39] exhibited the improved antimicrobial properties in composites. The Tar/PAN/Ag nanofibers showed higher antimicrobial activities (up to 39%) against Gram-positive Staphylococcus aureus ( S. aureus ) and Gram-negative Escherichia coli ( E. coli ) in comparison with the neat PAN nanofibers [39].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, different approaches (covalent grafting 22, 23 , co-encapsulation 20 , molecular cloning 21 , etc.) presented in the literature as strategies for broadening the activity of nisin are based on a synergy of the activity of nisin against Gram positive bacteria with the activity of another antimicrobial agent active against Gram negative bacteria (Ag nanoparticles 20 , other peptides, i.e., apidaecin 1b, oncocin 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…New strategies comprise novel formulations of lantibiotics, including their loading into various drug-delivery systems or deposition/binding to the biologically applied surfaces 19 , which enhance their stability and provide advanced biological functions (an example is loading nisin together with Ag nanoparticles within PDLLA/PEO polymeric fibers) 20 . A very interesting approach also considers the molecular cloning of different tails (using antimicrobial peptides effective against Gram negative bacteria) fused to the C terminus of nisin, which enabled stronger activity in E. coli 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies revealed that combining nisin nanofibers with other antimicrobial agents increased the inhibitory effect. Considering the enhanced efficacy of combined treatment,Ahire, Neveling, and Dicks (2015) synthesized nanofiber combinations through electrospinning nisin with a blend of 24 % (w/v) poly(D,L-lactide), poly(ethylene oxide) and silver nanoparticles, and the results showed increased inhibition of both Gram-positive and Gram-negative bacteria. The main disadvantage associated with nanofibers in the food industry is low throughput, which can be surpassed by their advantages and advanced applications.Further studies are required to demonstrate the workability of nanofibers in the food industry and other areas.…”
mentioning
confidence: 99%